Stalingrad - Horwitz, Dominique; Kretschmann, Thomas 1962-; Nickel, Jochen; Rudolph, Sebastian
In the spring of 1942, German troops advanced deep into the Soviet Union en route to Stalingrad. Hitler seriously misjudged the tenacity of the Red Army and was convinced that the city could be conquered before winter. Ordinarily foot soldiers, inadequately clothed and without sufficient food, struggled just to stay alive.